Assessing the influence of human settlements on the plant diversity in wetlands of Phobji and Gangtey, Bhutan - Lhamo, Pema; Kabir, Ahmedul; Uddin, Sayed Mohammad Nazim (Recent Research in Science and Technology, 2020)
Plant diversity in the wetlands of Phobji and Gangtey represents an important aspect of the overall wetland ecosystem. However, over the years, the increasing trend in population has initiated the building of many infrastructures and accommodations which lie at close proximity to the core wetland area. The plant diversity in human settled area and core undisturbed area was studied, with an objective to assess the influence of human settlement on the plant diversity. A belt transect method was used for the purpose of vegetation survey and Shannon Wiener diversity was calculated using the relative dominance. Plants were analyzed for their diversity, richness, dominance and invasive nature. Additionally, soil and water parameters were also tested to see the current situation of the pH and nutrient levels. A total of 136 species belonging to 39 families was identified in both the areas. The overall diversity index and species richness was found to be higher in the undisturbed areas. Soil analysis did not show much of a difference in physical and chemical parameters except for a slight difference in potassium content. Similarly, water parameters did not show much difference but only showed variation in calcium content. The findings of the study indicated towards the increasing influence of human settlement in the wetland.